2005
DOI: 10.1002/adma.200500539
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Bonded Ceramic Oxide Coatings on Carbon Nanotubes and Inorganic Nanowires

Abstract: Carbon nanotubes (CNTs) and inorganic nanowires constitute two important classes of one-dimensional materials. [1][2][3][4][5] Several studies on the synthesis, characterization, and manipulation of these materials have been reported.[6] Thus, several workers have prepared composites of these materials and studied their properties. [1,4,7,8] CNTs have been employed as templates for the preparation of nanotubes and nanowires of inorganic materials, especially of metal oxides. [4,[9][10][11][12][13][14][15][16] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 18 publications
1
80
0
Order By: Relevance
“…DWNT and SWNT nanotubes were functionalized with carboxyl groups in concentrated nitric acid (6 M) for 24 hours at 80°C [21][22][23]. The acid/NT mixture was subsequently washed with distilled water and centrifuged several times until their aqueous solution reached neutral pH.…”
Section: Methodsmentioning
confidence: 99%
“…DWNT and SWNT nanotubes were functionalized with carboxyl groups in concentrated nitric acid (6 M) for 24 hours at 80°C [21][22][23]. The acid/NT mixture was subsequently washed with distilled water and centrifuged several times until their aqueous solution reached neutral pH.…”
Section: Methodsmentioning
confidence: 99%
“…Metal oxide coated CNTs and inorganic nanowires can be prepared as shown in scheme 5 (Gomathi et al, 2005). The ceramic oxide coating provides improved compatibility with polar matrices as well as improved thermal stability of the nanotubes and nanowires.…”
Section: Functionalization Of Nanoreinforcementsmentioning
confidence: 99%
“…The ceramic oxide coating process for (a) carbon nanotubes and (b) metal oxide nanowires (from Gomathi et al, 2005).…”
Section: Functionalization Of Nanoreinforcementsmentioning
confidence: 99%
“…Hence, ALD film growth is self-limiting and based on surface reactions, which enables deposition control on the atomic scale. As an example, Gomathi et al used metal chloride precursors to coat acid-treated MWCNTs with TiO 2 and Al 2 O 3 [208]. Similarly, Javey et al demonstrated coatings of ZrO 2 as thin as 8 nm covering the top of horizontally attached SWCNTs for device applications [209].…”
Section: Atomic Layer Depositionmentioning
confidence: 99%